Digital Transformation of the Integrated Police Service Center (SPKT) as an Instrument for Protecting Reporters’ Rights in the Era of Bureaucratic Reform - Akbar, Taufik; Rafianti, Fitri; Siregar, Mhd. Azhali (International Conference Epicentrum of Economic Global Framework, 2026)
Receiving public reports and complaints. The ongoing digital transformation within the police institution carries significant consequences for public service mechanisms, particularly in the context of protecting reporters’ constitutional rights. This study aims to examine how the digital transformation of SPKT contributes as an instrument for protecting reporters’ rights within the framework of bureaucratic reform in Indonesia. The research method employed is normative legal research with a statutory approach (statute approach), conceptual approach (conceptual approach), and case approach (case approach). Legal materials were collected through library research on regulations, academic literature, and relevant policy documents. The findings indicate that although the digitalization of SPKT through the Dumas Presisi application and SPKT Online has facilitated access for reporters, its implementation still faces various structural and cultural obstacles, ranging from the digital divide and limited technological literacy among the public to suboptimal online protection of reporters’ data. This study concludes that strengthening technical regulations, enhancing police human resource capacity, and fostering cross-sectoral collaboration are necessary to ensure that the digital transformation of SPKT genuinely functions as an effective, equitable, and just instrument for protecting reporters’ rights.